PENGARUH KROMIUM HEKSAVALEN (VI) TERHADAP TINGKAT KELANGSUNGAN HIDUP IKAN NILA (OREOCHROMIS NILOTICUS) - AYU MARETHA OKA WIRES, EDELYNNA A.M.O. (LenteraBio: Berkala Ilmiah Biologi, 2012)
Chromium is a heavy metals, pollutants, and micronutrients that are important to the body. Type of chromium that has toxic effects to the organism is hexavalent chromium. This study aims to determine the effect of hexavalent chromium on the survival rate of tilapia (Oreochromis niloticus). Experimental studies conducted in the laboratory, using a Completely Randomized Design (CRD) with one treatment factor, namely the concentration factor. Concentrations of hexavalent chromium used is 0 ppm (control), 57,69 ppm, 59,94 ppm and 83,20 ppm. The results showed that hexavalent chromium significantly affect the survival rate of tilapia. The survival rate of tilapia in a row at a concentration of 57,69 ppm; 59,94 ppm, and 83,20 ppm for 54,78; 43,08, and 0,33. The conclusions of this study is that hexavalent chromium concentration of 57,69 ppm; 59,94 ppm, and 83,20 have a significant influence on the survival rate of tilapia